Draft Genome Sequence of the Endophytic Bacterium Variovorax paradoxus KB5, Which Has Antagonistic Activity against a Phytopathogen, Pseudomonas syringae pv. tomato DC3000 - Hong, Chi Eun (Genome Announc, 2017)
Variovorax paradoxus KB5, isolated from the inside of Arabidopsis thaliana leaves, showed antibacterial activity against the phytopathogen Pseudomonas syringae pv. tomato DC3000. Here, we report a draft genome sequence of V. paradoxus KB5, which contains a delftibactin-like nonribosomal peptide biosynthetic gene cluster.